Bioactivity of plants eaten by wild birds against laboratory models of parasites and pathogens - Bautista-Sopelana, Luis M.; Bolívar, Paula; Gómez-Muñoz, María Teresa; Martínez-Díaz, Rafael A.; Andrés, María Fe; Alonso, Juan Carlos; Bravo, Carolina; González-Coloma, Azucena (Frontiers in Ecology and Evolution, 2022)
Plants are not only used as energy and nutrient resources for herbivores. Plants can be ingested because of their activity against host parasites and other pathogens. This so-called medicinal role of plants is well reported in ethnopharmacology and under-reported in wild animals. More studies on wild animals are needed because any plant in the world contains bioactive compounds, and probably all plants, no matter how toxic they are, experience herbivory. For example, we tested the activity of extracts and essential oils from Papaver rhoeas and Echium plantagineum against a selection of laboratory pathogens because Great bustards Otis tarda preferred these plants during the mating season, with male fecal droppings showing a higher frequency of P. rhoeas particles than the fecal droppings of females. We hypothesized that P. rhoeas could be helpful for males in the mating season if any part of this plant harbors bioactivity against parasites and other pathogens. Males' immune system is weakened during the mating season because of their investment in secondary sexual characters and sexual display. As a first exploration of the bioactivity of these plants, we evaluated extracts of both plants against a sample of laboratory models, including a flagellated protozoon (Trichomonas gallinae), a nematode (Meloidogyne javanica) and a fungus (Aspergillus niger). Non-polar and polar extracts of the aerial parts of P. rhoeas, especially the extracts of flowers and capsules, and the extracts of leaves and flowers of E. plantagineum showed activity against nematodes and trichomonads. The bioactivity of plants against parasites could explain the foraging behavior of stressed animals. The chemical communication underpinning the capacity of fauna to recognize those plants is far less known.